Does Personalized Advertisement Influence Behavioral Intention and Customer Engagement? Study in Gen-Z Instagram Users - Rifelly Dewi Astuti; Luthfan Fadhila Henryanto Putra (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2023)
There is an increasing study on the effect of personalized advertising from the traditional approach, but few studies have examined the effect of social media advertising, especially Instagram. Using the partial least structural equation modeling (PLS-SEM) method, this study examines the effects of personalized advertising perceived by consumers (consisting of perceived personalization, ad credibility, ad skepticism, and ad avoidance) on Instagram toward the reaction of consumers’ attitudes and behavior. This present study involved 421 sample data of Gen-Z Instagram users who had used the social media application in recent weeks during the study. The findings of the study prove that personalized advertising can increase positive responses of consumers (e.g., increase the credibility and attitude of advertisements) and reduce their negative responses to advertisements (e.g., advertising skepticism and advertising avoidance). This positive response is proven to increase the likelihood of consumers buying and their involvement in personalized advertising. The implication and recommendation are also provided in this paper.Keywords: Personalized advertising, ad credibility, ad skepticism, ad avoidance, attitude towards advertising, Instagram, Gen-Z